2021
DOI: 10.5539/elt.v14n9p32
|View full text |Cite
|
Sign up to set email alerts
|

Possible Impact of Overseas Study on Language Ability and Motivation to Study English

Abstract: The present study explored whether two semester overseas study programs had any impact on participants’ language ability and motivation to study English. The language ability, L2 learning motivation and learning attitude of 65 Japanese university students participating in semester-long study abroad programs were measured pre departure and on their return. TOEIC listening and reading tests were used to measure students’ linguistic gains, and possible changes to students’ L2 motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…Cocca and Cocca (2019) investigated the predictability of affective variables and motivational intensity in language learners' academic achievement and their study revealed the significant relationship between learners' motivational intensity, their attitudes toward learning English and their language proficiency. Mori and Gobel (2021) studied the effect of studying abroad and learners' language ability and their motivational intensity. They found a strong correlation between learners' desire and their motivational intensity.…”
Section: Motivational Intensitymentioning
confidence: 99%
“…Cocca and Cocca (2019) investigated the predictability of affective variables and motivational intensity in language learners' academic achievement and their study revealed the significant relationship between learners' motivational intensity, their attitudes toward learning English and their language proficiency. Mori and Gobel (2021) studied the effect of studying abroad and learners' language ability and their motivational intensity. They found a strong correlation between learners' desire and their motivational intensity.…”
Section: Motivational Intensitymentioning
confidence: 99%
“…Highly motivated EFL learners are generally outstanding in academics and do not feel anxious and uneasy in English learning ( Carreira, 2011 ), while low motivation is considered as the main factor that reduces EFL learners’ learning effectiveness ( Lan, 2015 ). A high motivation for L2 learning, which indicates a high degree of effort spent on learning the language ( Lalonde and Gardner, 1985 ), is accompanied by remarkable persistence in L2 learning ( Mori and Gobel, 2021 ). English learners’ level of motivation is affected by their intrinsic interest, which enhances their pragmatic awareness and promotes their cultivating motivation ( Li et al, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A significant correlation was found between the desire and the motivational intensity of EFL learners who plan to study abroad. In contrast, the desire and the motivational intensity before departure were significantly related to their language listening and reading ability ( Mori and Gobel, 2021 ). Therefore, motivational intensity is important in measuring EFL learners’ motivation levels ( Papi and Abdollahzadeh, 2012 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations